ANALISIS PENERAPAN AKUNTANSI BERDASARKAN PSAK 105 PADA PEMBIAYAAN MUDHARABAH DI BMT SUMBER BAROKAH PULAU RAKYAT - Syahri Fadhilla; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
Mudharabah is a form of cooperation between the owner of the fund (shahibul mal) and the manager of the fund (mudharib) in which the business profits are divided according to the mutual agreement made at the beginning of the agreement. The formulation of the problem in this study is how the mudharabah financing mechanism in BMT Sumber Barokah Pulau Rakyat. The purpose of this study was to determine whether the application of accounting treatment regarding the recognition, measurement, presentation and disclosure of mudharabah financing at BMT Sumber Barokah Pulau Rakyat was in accordance with PSAK 105. The research method used was a qualitative method using descriptive analysis. Data collection techniques used by the author are interviews and documentation. The results of the study stated that the accounting treatment of mudharabah financing at BMT Sumber Barokah Pulau Rakyat was carried out properly and in accordance with PSAK 105 starting from the recognition, measurement, presentation, and disclosure of financing.